ACARA MARTUMPOL ADAT BATAK TOBA (KAJIAN SEMIOTIKA) - Frederica, Frederica; Syafrial, Syafrial; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research entitled Event Martumpol Adat Batak Toba (Semiotics Review). This study aims to clearly understand the sign presented in the event of customary Batak Toba martumpol. This type of research is qualitative with semiotic approach. The result of this research is a descriptive narrative. The data is accompanied by interpretation that interprets all aspects of the culture. In accordance with these characters, this research tries to get information that is complete about one of indigenous ethnic Batak Toba tribe. The validity of data is inscribed by interview technique based on one stage of marriage of Batak Toba people. Then the data were analyzed by identifying and classifying the data on the Toba Batak custom martumpol event. The results of the research, found the mark in the event of custom martumpol Batak Toba amounted to 13 data, the data division is (1) index amounted to 5 data, (2) symbols amounted to 7 data and (3) icons amounted to 1 data.Keywords: Semiotics, Martumpol Ceremony, Batak Toba